Levantamento de patentes sobre a planta Moringa oleifera no Brasil e no mundo - SOUSA, Dayane Nunes (2016)
Actually, one of the current concerns in the pharmaceutical, the cosmetics and food industries is the development of products with the largest number of natural, especially those of vegetable origin. Brazil has the greatest biodiversity of the planet and almost 13% of about 1.9 million catalogued plant species are found in the country. The surveyed plant Moringa oleifera has different biological properties such as antimicrobial activity, antitrypanosomal, antihypertensive, antiulcer, hypocholesterolemic, antispasmolytic, antioxidant, anti-inflammatory and anti-cancer. This plant has high nutritional value, especially in relation to the leaves, which are important sources of vitamin A, C and iron, is used to purify water for human consumption and has great economic importance in the production of various commodities such as oil, food, spices and medicines. This study aims to assess the use of M. oleifera as regards deposits and registration of patents based on information collected between the period of October 1995 to October 2015 using patent databases from the World Intellectual Property Organization (WIPO), the European Patent Office (EPO) and the National Institute of Industrial Property (INPI). The investigations performed in this study were the number and the filing date, the title, the abstract, the applicant, the inventor, the international classification of patents and technological focus. Through this study, we can conclude that in Brazil the number of patent applications involving the M. oleifera plant is lower than other countries. It is believed that these low values are caused by the low investment in R & D and the long waiting period during the patenting process, which ends up discouraging the researchers/inventors. This leads to a loss of opportunities for trade, as the analysis of patent documents allows the development of technological skills and opportunities to work and commercially explore the area.